FT-IR and Raman Spectroscopic and Quantum Chemical Studies of Zinc Halide Complexes with 2,2 '-Biquinoline - Özel, Ayşen E.; Keçel, Serdal; AKYÜZ, SEVİM (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2008)
The molecular structure, vibrational frequencies and the corresponding vibrational assignment of Zn(biq)X-2 (X = CI and Br; biq = 2,2'-biquinoline) have been studied by employing the hybrid density functional theory (B3LYP) method and the complete basis set (DFT) method together with the 6-31G(d,p) basis set for X = Cl and Br. The FT-IR (400-4000 cm(-1)) and Raman (100-3200 cm(-1)) spectra of compounds were recorded and compared with that of the calculated spectra, which allowed authors to assign most of the observed bands. It was demonstrated that cis conformer is suitable for the Zn(biq)X2 Compounds. The fundamental vibrational modes were characterized by their total energy distribution. The coordination effects on vibrational wavenumbers of biq were discussed in detail. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Ab Initio Calculations; DFT; 2,2 '-Biquinoline; Halide Complexes; Vibrational Frequencies; Normal-Coordinate Analysis; Biquinoline; Quinoline; Spectra; Ab Initio Hesaplamaları; Halojenür-Kompleksleri; Titreşim Frekansları; Analizi Koordinat Normal; Kinolin; Spektrumları